Dental manifestations in bariatric patients: review of literature - Carolina Silveira Barbosa; Gabriel Salles Barbério; Vinicius Rizzo Marques; Vitor de Oliveira Baldo; Marília Afonso Rabelo Buzalaf; Ana Carolina Magalhães (University of São Paulo, 2009)
The rate of bariatric surgery has significantly risen in the past decade as an increasing prevalence of extreme obesity can be observed. Although bariatric surgery is an effective therapeutic modality for extreme obesity, it is associated with risk factors affecting also oral health. Based on an overview of the current literature, this paper presents a summary of dental manifestations in bariatric patients. Bariatric surgeries are associated with an increased risk for gastro-esophageal reflux which in turn might account for the higher amount of carious and erosive lesions observed in bariatric patients. As a result, also dentin hypersensitivity might be observed more frequently. The current data indicate that recommended postsurgical meal patterns and gastric reflux might increase the risk for dental lesions, particularly in the presence of other risk factors, such as consumption of sweet-tasting foods and acidic beverages. Further research is needed to evaluate the correlation of bariatric surgery and the development of dental diseases.